Effect of prothioconazole-based fungicides on Fusarium head blight, grain yield and deoxynivalenol accumulation in wheat under field conditions - Haidukowski, M.; Visconti, A.; Perrone, G.; Vanadia, S.; Pancaldi, D.; Covarelli, Lorenzo; Balestrazzi, R.; Pascale, M. (Mediterranean Phytopathological Union and Firenze University Press, 2012)
The effect of triazole-based treatments on Fusarium head blight (FHB), grain yields and the accumulation of deoxynivalenol (DON) in harvested wheat kernels was evaluated by means of twenty multi-site field experiments performed during five consecutive growing seasons (from 2004-2005 to 2008-2009) in Italy. Fungicide treatments were carried out on different cultivars of common wheat (cv. Serio, Blasco, Genio and Savio) and durum wheat (cv. Orobel, Saragolla, San Carlo, Levante, Duilio, Karur and Derrik) after artificial inoculation with a mixture of toxigenic Fusarium graminearum and F. culmorum strains. The application of fungicides containing prothioconazole (Proline® or Prosaro®) at the beginning of anthesis (BBCH 61) resulted in a consistent reduction of FHB disease severity (by between 39 and 93%) and DON levels in wheat kernels (by between 40 and 91%) and increased wheat yields (from 0.4 to 5.6 t ha-1, average 2.2 t ha-1), as compared to the untreated/inoculated control. Fungicides containing tebuconazole (Folicur® SE) and cyproconazole plus prochloraz (Tiptor® Xcell) showed a reduced effectiveness compared with prothioconazole-based treatments. All fungicide treatments were more effective in reducing DON and increasing grain yields of common wheat than durum wheat. Results showed that the application of fungicides containing prothioconazole at the beginning of anthesis provided a strong reduction of FHB disease, allowing both an increase in grain yields and a considerable reduction of DON content in wheat kernels. © Firenze University Press.